Mengkaji Dampak Literasi Ekonomi Terhadap Pola Konsumsi Remaja Akhir - Putri, Kusbandiyah; Astuti, Sri; Safitri, Camelia (Jurnal Ecogen, 2024)
This consumptive behavior is often found in the lives of teenagers who live in urban areas. Because teenagers in urban areas live a complex social life, individuals compete to consume things to gain identity through what they consume. Economic literacy helps reduce a person's consumptive behavior. This research aims to determine the influence of economic literacy on the consumptive behavior of late adolescents. This research uses an associative quantitative method with a non-probability sampling method using purposive sampling. The sample in this study amounted to one hundred and fifteen respondents. This research surveyed by distributing online questionnaires to examine economic literacy and consumer behavior. Statistical analysis tests were carried out with the help of SPSS twenty-six zero points software. The research results show that in testing the hypothesis, H0 is accepted and Ha is rejected, and there is no significant influence between economic literacy and consumer behavior in Rawalumbu. It can be concluded that high or low economic literacy in the late teens in Rawalumbu does not influence consumer behavior.